Early Warning System for Penalty Constrained Financial Risks of Enterprises under Diversified Investment - Yongyong Zhu (Journal of Mathematics)
Based on the understanding of the main types and purposes of enterprise diversification investment, this paper conducts an in-depth analysis of the environmental, structural, and scale risks of enterprise diversification investment and uses this as the basis for the effective construction of a risk prevention model. It can help enterprises effectively avoid investment risks, avoid bringing huge economic losses to enterprises, and help lay a good foundation for the positive development of enterprises. With the rapid development of social economy, enterprises must realize diversified investment if they want to improve their market economy status. However, due to many factors, they face greater economic risks and even cause serious economic losses to enterprises. Therefore, effective measures must be taken to prevent risks and promote the sustainable development of enterprises so as to obtain more economic benefits.